Biofunctional roles of estrogen in coronavirus disease 2019: Beyond a steroid hormone - Wang, Zhong-Ping; Hua, Mao; Jiu, Tai; Ge, Ri-Li; Bai, Zhenzhong (Frontiers in Pharmacology, 2022)
The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), epidemic poses a major global public health threat with more than one million daily new infections and hundreds of deaths. To combat this global pandemic, efficient prevention and management strategies are urgently needed. Together with the main characteristics of COVID-19, impaired coagulation with dysfunctions of the immune response in COVID-19 pathophysiology causes high mortality and morbidity. From recent clinical observations, increased expression of specific types of estrogen appears to protect patients from SARS-CoV-2 infection, thereby, reducing mortality. COVID-19 severity is less common in women than in men, particularly in menopausal women. Furthermore, estrogen levels are negatively correlated with COVID-19 severity and mortality. These findings suggest that estrogen plays a protective role in the pathophysiology of COVID-19. In this review, we discuss the potential roles of estrogen in blocking the SARS-CoV-2 from invading alveolar cells and replicating, and summarize the potential mechanisms of anti-inflammation, immune modulation, reactive oxygen species resistance, anti-thrombosis, vascular dilation, and vascular endothelium protection. Finally, the potential therapeutic effects of estrogen against COVID-19 are reviewed. This review provides insights into the role of estrogen and its use as a potential strategy to reduce the mortality associated with COVID-19, and possibly other viral infections and discusses the possible challenges and pertinent questions.